The Wreath of Athletic Victory and its Moral Symbolism - Goggaki, K. (International Journal of Physical Education, 2002)
The wreath with which the victors in the Olympic Games are crowned today is neither a contemporary custom nor a tradition that simply accompanies a formal ritual. On the contrary, this tradition can be traced back into the distant past, with its roots in very old customs, back when truth and reason were sweetly mixed with imagination and myth. This paper follows the importance of the crowning of the victor in athletic competitions, or games, linking this event with its multiple manifestations in various events of modern-day cultural reality. The wreath of the competition winners has, as such, different moral symbolisms, some of which have been lost with the passage of time while others survived and have been passed on to the present. These symbolisms trace back to the age of mythology, back to when every natural phenomenon took on metaphysical dimensions. These magical interpretations are the remnants of tree worship, then when the non-civilized man believed in the theory of "animism". Later, these theories of the beneficial effects of the sacred branch or protection from bad influences were concealed under an agricultural nature of the economy and corresponding beliefs were incorporated. Later, animism evolved into poly-theism, giving religious content to these perceptions, such as that of forgiveness, an idea that does not belong to the field of magic, but religion. Other important values are those of chastity, of catharsis, and the symbol of world peace, that survive to our days, despite their tough competition from the financial value that athletic victories mean today. In general, however, the symbolisms and above interpretations of the competition victor’s crowning wreath confirm the theory that athletics is a “microcosm”, and a mirror of social development that reflects the course of society.